Increasing in vivo iron loading of archaeoglobus fulgidus ferritin (afftn) transformed E.coli by overexpressing the ferrous transporter, FeoB - Tan, Ker Jia. (2011)
Research has proven iron-loaded Archaeoglobus fulgidus ferritin (AfFtn) as a good T2 MRI contrast agent and that higher concentrations of iron in iron-loaded AfFtn enhanced T2 imaging contrasts. Works on increasing in vivo AfFtn iron loading using E. coli as a biofactory have been performed by increasing the extracellular ferrous (Fe2+) concentrations. However, the amount of iron loaded achieved at 1400 Fe/24-mer is still far from the ~7200 Fe/24-mer stoichiometric value. It was hypothesized that the E.coli cytoplasmic membrane is the limiting factor to high intracellular Fe2+ concentrations. This project investigated the possibility of increasing ferrous iron permeability of the E.coli cytoplasmic membrane by overexpressing its ferrous transporter, FeoB, in order to increase the intracellular Fe2+ concentration and subsequently increasing in vivo iron loading into cytoplasmic AfFtn. AfFtn and FeoB from BL21 (DE3) were co-expressed in E.coli BL21 (DE3) CodonPlus-RIL cells. FeoB was tagged with green fluorescent protein (GFP) to detect its correct expression. Iron loading was compared across FeoB-GFP-AfFtn, FeoB-AfFtn and AfFtn transformed E.coli at 2 and 4 hours of 10mM Fe2+ iron loading. Results obtained shown that a ~3 fold increase in AfFtn iron loading was achieved when FeoB-GFP was co-expressed with AfFtn. Thus, overexpression of ferrous transporter FeoB increased the efficiency of in vivo iron nanoparticles production using E.coli as a biofactory.